Detonation processes application to increase thermal efficiency in gas turbine cycles: Case study for hydrogen enriched fuels - Robson A. Schneider; Cesar Celis; Andrés Z. Mendiburu (International Journal of Thermofluids)
This work describes a thermodynamic comparison of the thermal efficiency of gas turbine engines featuring a conventional combustion chamber and a detonation combustion chamber, using methane, ethanol and mixtures of both ethanol and hydrogen and methane and hydrogen as fuels. The composition of gases was determined by the minimization of the Gibbs free energy, whereas temperature, pressure, and velocity of detonation waves were determined by the Chapman-Jouguet theory. The results obtained here show that the DCC gas turbine cycle has a higher net work output and thermal efficiency than the CCC gas turbine cycle for all fuels studied in this work. The maximum thermal efficiency obtained with the DCC gas turbine cycle is indeed 57.22 %, which represents a 53.75 % improvement over the maximum thermal efficiency obtained with the CCC gas turbine cycle (which has a peak thermal efficiency of 37.22 %), under the same pressure ratio and turbine inlet temperature.